Zambia Mining Investment and Governance Review - World Bank (Washington, DC, 2016)
The Zambia Mining Investment and Governance Review (MInGov) collects and shares information on mining sector governance, its attractiveness to investors and how its activities affect national development. It reviews sector performance from the perspective of three main stakeholder groups– government, investors in the mining value chain and civil society – and identifies gaps between declared and actual government policy and practice. The review's key findings are: Performance across the value chain is strongest in topics most closely associated with mining and which are related to the content of laws and regulations, though implementation of these is wanting in some instances; Sector development is constrained by a number of bottlenecks; According to investors, a number of areas are constraining mining investment and returns; The three key stakeholder groups agree on a number of topics they believe are particularly important to strengthen sector governance, investment and development impact; Civil society believes there is a number of weaknesses sector governance, including the poor handling of environment and social impacts of mining; problems with human rights associated with the sector; ineffective development planning as it relates to mining; issues concerning land access, compensation and resettlement; and the absence of revenue sharing between national and local government.MInGov’s methodology focuses on the status of governance and investment conditions in the mining sector from the perspective of stakeholders, and as reported in primary and secondary sources. However, less-well covered areas include the quality of its infrastructure services, the security of property from theft, the underlying strength of institutions, and ways to enhance mining’s contribution to local and national development.This report presents data on mining investment and governance indicators for Zambia that are current as of October 2015.